Proteomic characterization of eurycoma longifolia and its application in validating tongkat Ali herbal products / Venoos Iman - Iman, Venoos (2011)
Eurycoma longifolia commonly known as “Tongkat Ali” in Malaysia is claimed to have aphrodisiac properties and has been widely used in Malay traditional medicine. An aphrodisiac is defined as a substance that increases sexual activity and libido and/or improves sexual performance. These claims have led to a vast number of “Tongkat Ali” products being marketed without proper authentication. There was therefore a need to characterize the proteins in these commercial Tongkat Ali herbal products using biomarkers to establish the authenticity of the claims. The important chemical components in Eurycoma longifolia are eurycomanol, eurycomanone and eurycomalactone. However they are not linked to the aphrodisiac properties, instead suspected to be protein base. In this study a total of 23 Ministry Of Health (MOH) approved and 6 non-MOH approved samples were sourced and screened for markers previously developed using two dimensional electrophoresi (2-DE). The markers were denoted as A and B with appearances between 12 to 14 kDa in 2-DE performed on IPG strips of 3-10 (7 cm) for the 1st dimensional electrophoresis, while 12.5% homogenous gel was used for the 2nd dimensional electrophoresis in silver stain. The results of the study confirmed that 18 of the 29 products tested were authentic with the presence of both biomarkers A and B, while 11 (a combination of both approved and non-MOH approved products) did not show presence of biomarkers. This enabled authentication of the products tested. The protein markers in addition to the existing chemical marker, Eurycomanone, may serve to be useful in authenticating genuine Tongkat Ali products.